Strategic management accounting: information application areas and instruments - Medeckytė, Kamilė; Tamulevičienė, Daiva (Buhalterinės apskaitos teorija ir praktika, 2020)
he application of strategic management accounting instruments in corporate governance is a significant tool for gaining a competitive advantage, increasing the existing market share, and improving the company’s performance. The article examines the development, concept, and significance of strategic management accounting. There are five areas of strategic management accounting: 1) costing; 2) planning, control, and performance measurement; 3) strategic decision-making; 4) competitor accounting; 5) customer accounting. The main instruments of each area, their advantages, challenges of implementation in enterprise management, and benefits for the efficiency of the organization have been identified.
Keywords: strategic management accounting; strategic management accounting fields; strategic management accounting instruments